2010
DOI: 10.1002/ca.21014
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the superior labrum and biceps origin in the fetal shoulder

Abstract: The presence of a sublabral recess has been observed in adult shoulders. It is unclear whether this occurrence is a developmental variation or is acquired. The primary objective of the study was to determine if a cleft exists between the superior labrum and the superior cartilaginous glenoid anlage during the second trimester. The secondary objective was to define the origin of the long head of the biceps in the human fetus in the second trimester. Shoulders of 11 fetuses, 11-20 weeks old, were sectioned in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The glenoid labrum was sparsely vascularized without any configurative pattern of distribution and the vascularity was observed to decrease with age. 24 In contrast, one study 25 reported that the vascular channels proliferating inside the glenoid labrum and glenoid bone increased with gestational age. The current study observed that the consistency of the superior half of the glenoid labrum was rubbery in 97.86% ( n = 137) and firm in 2.14% ( n = 3) of specimens, whereas the entire inferior half was firm.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The glenoid labrum was sparsely vascularized without any configurative pattern of distribution and the vascularity was observed to decrease with age. 24 In contrast, one study 25 reported that the vascular channels proliferating inside the glenoid labrum and glenoid bone increased with gestational age. The current study observed that the consistency of the superior half of the glenoid labrum was rubbery in 97.86% ( n = 137) and firm in 2.14% ( n = 3) of specimens, whereas the entire inferior half was firm.…”
Section: Discussionmentioning
confidence: 95%
“…The glenoid labrum was sparsely vascularized without any configurative pattern of distribution and the vascularity was observed to decrease with age. 24 In contrast, one study 25 reported that the vascular channels Alashkham et al…”
Section: Discussionmentioning
confidence: 96%
“…Some authors have shown in adults [Standring, 2008] and in fetuses [Aboul-Mahasen and Sadek, 2002;Lapner et al, 2010] that the LHBT originates from the glenoid labrum and the supraglenoid tubercle. Several authors found the main origin of the LHBT in the supraglenoid tubercle (25% of cases [Pal et al, 1991] and 40-60% of cases [Vangsness et al, 1994]), and there are studies that report that in 6.4% of cases the LHBT originates only from the supraglenoid tubercle [Demondion et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…However, developmental studies on the origin of the LHBT from the glenoid labrum and the scapula are scarce. Some studies describe the LHBT as originating from the glenoid labrum and the supraglenoid tubercle in all specimens, both in fetuses [Aboul-Mahasen and Sadek, 2002;Lapner et al, 2010] and in adults [Pal et al, 1991;Tuoheti et al, 2005]. Other authors have stated that the LHBT is not attached to the supraglenoid tubercle [Gigis et al, 1995] and even have described it as originating only from the supraglenoid tubercle in 6.4% of the cases [Demondion et al, 2001].…”
Section: Introductionmentioning
confidence: 99%